AB0017 Impact of Disease Susceptibility Genes on Progression of Joint Destruction in Japanese Patients with Rheumatoid Arthritis. (10th June 2014) - Yoshida, S.; Ikari, K.; Yano, K.; Toyama, Y.; Taniguchi, A.; Yamanaka, H.; Momohara, S.
Abstract : Background: Disease severity of rheumatoid arthritis (RA) is objectively measured by radiographic joint damage, which is reflective of the cumulative burden of inflammation. To date, several genetic risk loci for progression of joint destruction have been reported in European multi-cohort studies. 1 However, genetic predisposition factors for progression of joint destruction remains less understood in Asian populations. We demonstrated that PADI4 and HLA-DRB1 of susceptibility genes for RA are genetic risks for progression of joint destruction in Japanese patients with RA. 2 Recently, a genome-wide association study meta-analysis in a total of more than 100, 000 subjects of European and Asian ancestries discovered 42 novel susceptibility loci for RA, of which 6 were specific to Asian ancestry at genome-wide level of significance. 3 We investigated whether these 6 genes were associated with progression of joint destruction in Japanese patients with RA. Objectives: The purpose of this study was to test the impact of 6 novel disease susceptibility genes on progression of joint destruction in Japanese patients with RA. Methods: This study included 865 Japanese patients with RA for whom Sharp/van der Heijde scores (SHS) of hands were available at a disease duration of 5 years. DNA samples of the subjects were obtained from the Institute of Rheumatology Rheumatoid Arthritis cohort study (IORRA) DNA collection. All of the patients who donated DNA samples consented to participate in this study approved by the Tokyo Women's Medical University Genome Ethics Committee, and satisfied the American College of Rheumatology 1987 revised criteria for the classification of RA. Six single nucleotide polymorphisms (SNPs) reported in the recent genome-wide association study meta-analysis 3 were selected and genotyped in the DNA samples: rs227163, in TNFRSF9 ; rs9498368, in PPIL4 ; rs726288, in SFTPD ; rs3783782, in PRKCH ; rs2469434, in CD226 ; rs10465436, in P2RY10 . Multivariate linear regression analyses were performed in order to examine the association of each SNP with the estimated yearly radiographic progression of joint destruction in the first 5 years after onset of RA. Adjustments were made for gender, age of onset, anti-citrullinated peptide antibody status and year of disease onset. All SHS were log-transformed to obtain a normal distribution. Results: Multivariate linear regression analyses revealed that all SNPs tested in this study were not associated with progression of joint destruction. Conclusions: We could not confirm the association between novel RA susceptibility genes and progression of joint destruction. Disease susceptibility genes outside the HLA locus might have a limited impact on progression of joint destruction. References: Knevel R, et al. Association of variants in IL2RA with progression of joint destruction in rheumatoid arthritis. Arthritis Rheum. 2013 Jul;65(7):1684-93. doi: 10.1002/art.37938. Suzuki T, et al. PADI4 and HLA-DRB1 are genetic risks for radiographic progression in RA patients, independent of ACPA status: results from IORRA cohort study. PLoS One. 2013;8(4):e61045. doi: 10.1371/journal.pone.0061045. Epub 2013 Apr 8. Okada Y, et al. Genetics of rheumatoid arthritis contributes to biology and drug discovery. Nature. 2013 Dec. doi: 10.1038/nature12873. [Epub ahead of print] Acknowledgements: We thank all DNA donors for making this study possible. We appreciate all the members of Institute of Rheumatology, Tokyo Women's Medical University for their effort on the IORRA cohort. We are also grateful to Ms Kaori Arai for her technical assistance. Disclosure of Interest: S. Yoshida: None declared, K. Ikari Grant/research support: Pfizer Japan Inc., Takeda Pharmaceutical Co. Ltd., Speakers bureau: Abbvie Japan Co., Ltd., Asahikasei Pharma Corporation, Astellas Pharma Inc., Eisai Co., Ltd., Kaken Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Corporation, Taishotoyama Pharmaceutical Co., Ltd. Y., K. Yano: None declared, Y. Toyama: None declared, A. Taniguchi: None declared, H. Yamanaka Grant/research support: Abbott, AbbVie, Asahikasei, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taishotoyama, Takeda, Teijin, Consultant for: Abbott, AbbVie, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, Mitsubishi Tanabe, Nippon Kayaku, Pfizer, Takeda, Teijin., Speakers bureau: Abbott, AbbVie, Astellas, Bristol-Myers Squib, Chugai, Eisai, Mitsubishi Tanabe, Pfizer, Takeda, Teijin.S., S. Momohara: None declared DOI: 10.1136/annrheumdis-2014-eular.3156